Molecular characterization of selected endophytic fungi isolate IDGG 3 leaf galing galing (cayratia trifolia L.) with the polymerase chain reaction method - Wirada, Nurwinda; Fitriana, Fitriana; Rusli, Rusli (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Background: Endophytic fungi live in plant tissues and are usually not harmful to their host plants. One of the host plants for endophytic fungi is bush grape leaves (Cayratia trifolia L.). Objective: The research aimed to determine the molecular characteristics of the endophytic fungi isolates selected IDGG 3 of bush grape leaves. Methods: The test used the polymerase chain reaction method to determine the species-level characteristics using internal transcribed spacers (ITS) 1 and 4. The DNA band was successfully amplified with 500 base pairs with 3000 markers. Results: The fungi isolates selected IDGG 3 of bush grape leaves in molecular identification based on the Basic Local Alignment Search Tool (BLAST) analysis on Genebank NCBI that the IDGG 3 samples of bush grape leaves had a similarity level of 99%, namely Fusarium incarnatum JL5-2, Fusarium incarnatum JL3-4- 1, Fusarium incarnatum CBB-2, Fusarium incarnatum JL3-3, Fusarium incarnatum CBA-3, Fusarium incarnatum CBB-1, Fusarium incarnatum CBA-2, Fusarium chlamydospore, Fusarium cf. Incarnatum, and Fusarium sp. Conclusion: The results of the molecular characteristics of the selected endophytic fungi isolate IDGG 3 galing-galing leaves (Cayratia trifoliata L.) have the closest degree of kinship with the species Fusarium incarnatum JL3-4-1. The importance of the PCR method in the molecular characterization of endophytic fungi, as well as opening opportunities for further exploration of the biotechnological potential of endophytic fungi from Cayratia trifolia L.